Educational Intervention Changes College Students' Attitudes toward Prescription Opioid Drug Use. (3rd February 2020) - Johnson, Evan C.; Huffman, Ainsley E.; Yoder, Hillary A.; Bordelon, Nicole M.; Sewczak-Claude, Gretchen; Smith, Derek T.
Abstract: Background: More than 47, 000 people in the United States died from opioid drug overdoses in 2017. Among college students, opioid drugs are the second most abused drug. Objective: This study aimed to examine if an educational intervention impacted college students' attitudes towards prescription opioid drugs (POD). Methods: Two hundred forty-two participants (72 males, 21 ± 3 years) from an American university participated. After collecting demographic data (questionnaire 1; Q1), investigators recited a narrative in which the protagonist was injured and prescribed POD. Next, participants rated their agreement on 10 Likert prompts and two visual analog scales (VAS) before (Q2) and after (Q3) an educational intervention, then noted (Q4) which topics were most or least influential in any changed responses. Results: 7/10 Likert prompts (all p < 0.002) and both VAS (both p < 0.001) changed between Q2 and Q3. Educational intervention topics related to risk were most influential and topics related to alternative therapies were least influential. Conclusion/Importance: Educational interventions may be beneficial for college students. Any interventions that are employed should focus on risks associated with POD use.